Chronic and Asymptomatic Diffuse Alveolar Haemorrhage with Microscopic Polyangiitis: A Case Report and Review of the Literature - Hiroki Tashiro; Koichiro Takahashi; Hironori Sadamatsu; Masaru Uchida; Shinya Kimura; Naoko Sueoka-Aragane (Case Reports in Rheumatology)
Diffuse alveolar haemorrhage (DAH) is one of the major causes of death in microscopic polyangiitis (MPA) patients, because of acute respiratory failure with various respiratory symptoms. We, herein, present a case of chronic and asymptomatic DAH in a patient with MPA who was diagnosed by fibreoptic bronchoscopy. The patient showed localized reticular shadows, without any respiratory symptoms, and absence of inflammatory reactions, such as fever and CRP elevation, which is atypical for DAH. Three months after appearance of the lung abnormalities, DAH with MPA was diagnosed by fibreoptic bronchoscopy. She was initially treated with only corticosteroids and has thereafter been maintained with corticosteroids and azathioprine without relapse to date. We reviewed the literature for similar cases and opined that physicians should perform fibreoptic bronchoscopy in MPA patients with chronic lung abnormalities and anaemia to identify DAH, even if the patients show no respiratory symptoms and in the absence of inflammatory reactions.